Oppressive Governments, Dependence on the United States and Anti-American Terrorism - Gries, Thomas; Meierrieks, Daniel; Redlin, Margarete (Oxford Economic Papers)

Erfolg durch Persönlichkeit? Der Einfluss der Markenpersönlichkeit auf den Zusammenhang von Reputation und Unternehmenserfolg - Fanasch, Patrizia

Die Veränderung des Mobilfunkmarktes durch die Discountanbieter - Walczok, Gregor Paul

Learning Boolean Specifications - Bubeck, Uwe; Kleine Büning, Hans (Artificial Intelligence)
In this paper we consider an extended variant of query learning where the hidden concept is embedded in some Boolean circuit. This additional processing layer modifies query arguments and answers by fixed transformation functions which are known to the learner. For this scenario, we provide a characterization of the solution space and an ordering on it. We give a compact representation of the minimal and maximal solutions as quantified Boolean formulas and we adapt the original algorithms for exact learning of specific classes of propositional formulas.
Keywords: Query learning; Propositional logic

Evaluation von Bildverarbeitungsalgorithmen in heterogenen Rechenknoten - Knorr, Christoph

A Domain-Specific Modeling Language for Electric Vehicle Batteries - Klör, Benjamin; Bräuer, Sebastian; Beverungen, Daniel; Monhof, Markus (Proceedings of the 12. International Conference on Wirtschaftsinformatik 2015 (WI 2015))

Extending Battery Management Systems for Making Informed Decisions on Battery Reuse - Monhof, Markus; Beverungen, Daniel; Klör, Benjamin; Bräuer, Sebastian (New Horizons in Design Science: Broadening the Research Agenda)

Neue Bildungslandschaften - Kommunales Bildungsmanagement als Zukunftsaufgabe - Euler, Dieter; Sloane, Peter F. E. (Zeitschrift für Berufs-und Wirtschaftspädagogik)

Die Bedeutung subjektiver Sichtweisen für die Implementierung betrieblicher Lernkultur - Fischer, Christoph; Harteis, Christian (Informelles Lernen, Annäherungen - Problemlagen - Forschungsbefunde)
Keywords: Epistemische Überzeugungen; learning culture

Effects of age, gender and occupation on perceived workplace learning support - Harteis, Christian; Billett, Stephen; Goller, Michael; Rausch, Andreas; Seifried, J{\ (International journal of training research)

Bedingungsfaktoren beruflichen Könnens - Harteis, Christian (Konzepte und Ergebnisse ausgewählter Forschungsfelder der beruflichen Bildung)

A Shared Task on Argumentation Mining in Newspaper Editorials - Kiesel, Johannes; Al-Khatib, Khalid; Hagen, Matthias; Stein, Benno (Proceedings of the 2nd Workshop on Argumentation Mining)

A Shared Task on Argumentation Mining in Newspaper Editorials - Kiesel, Johannes; Al-Khatib, Khalid; Hagen, Matthias; Stein, Benno (Proceedings of the 2nd Workshop on Argumentation Mining)

Sentiment Flow - A General Model of Web Review Argumentation - Wachsmuth, Henning; Kiesel, Johannes; Stein, Benno (Proceedings of the 2015 Conference on Empirical Methods in Natural Language Processing)

Planar prism spectrometer based on adiabatically connected waveguiding slabs - Civitci, F.; Hammer, Manfred; Hoekstra, H.J.W.M. (Optics Communications)
The device principle of a prism-based on-chip spectrometer for TE polarization is introduced. The spectrometer exploits the modal dispersion in planar waveguides in a layout with slab regions having two different thicknesses of the guiding layer. The set-up uses parabolic mirrors, for the collimation of light of the input waveguide and focusing of the light to the receiver waveguides, which relies on total internal reflection at the interface between two such regions. These regions are connected adiabatically to prevent unwanted mode conversion and loss at the edges of the prism. The structure can be fabricated with two wet etching steps. The paper presents basic theory and a general approach for device optimization. The latter is illustrated with a numerical example assuming SiON technology.
Keywords: tet_topic_waveguide

Full Resonant Transmission of Semiguided Planar Waves Through Slab Waveguide Steps at Oblique Incidence - Hammer, Manfred; Hildebrandt, Andre; Förstner, Jens (Journal of Lightwave Technology)
Sheets of slab waveguides with sharp corners are investigated. By means of rigorous numerical experiments, we look at oblique incidence of semi-guided plane waves. Radiation losses vanish beyond a certain critical angle of incidence. One can thus realize lossless propagation through 90-degree corner configurations, where the remaining guided waves are still subject to pronounced reflection and polarization conversion. A system of two corners can be viewed as a structure akin to a Fabry-Perot-interferometer. By adjusting the distance between the two partial reflectors, here the 90-degree corners, one identifies step-like configurations that transmit the semi-guided plane waves without radiation losses, and virtually without reflections. Simulations of semi-guided beams with in-plane wide Gaussian profiles show that the effect survives in a true 3-D framework.
Keywords: tet_topic_waveguide

Text Analysis Pipelines - Towards Ad-hoc Large-scale Text Mining - Wachsmuth, Henning

Unveiling Nanometer Scale Extinction and Scattering Phenomena through Combined Electron Energy Loss Spectroscopy and Cathodoluminescence Measurements - Losquin, Arthur; Zagonel, Luiz F.; Myroshnychenko, Viktor; Rodríguez-González, Benito; Tencé, Marcel; Scarabelli, Leonardo; Förstner, Jens; Liz-Marzán, Luis M.; García de Abajo, F. Javier; Stéphan, Odile; Kociak, Mathieu (Nano Letters)
Plasmon modes of the exact same individual gold nanoprisms are investigated through combined nanometer-resolved electron energy-loss spectroscopy (EELS) and cathodoluminescence (CL) measurements. We show that CL only probes the radiative modes, in contrast to EELS, which additionally reveals dark modes. The combination of both techniques on the same particles thus provides complementary information and also demonstrates that although the radiative modes give rise to very similar spatial distributions when probed by EELS or CL, their resonant energies appear to be different. We trace this phenomenon back to plasmon dissipation, which affects in different ways the plasmon signatures probed by these techniques. Our experiments are in agreement with electromagnetic numerical simulations and can be further interpreted within the framework of a quasistatic analytical model. We therefore demonstrate that CL and EELS are closely related to optical scattering and extinction, respectively, with the addition of nanometer spatial resolution.
Keywords: tet_topic_plasmonics

How planar optical waves can be made to climb dielectric steps - Hammer, Manfred; Hildebrandt, Andre; Förstner, Jens (Optics Letters)
We show how to optically connect guiding layers at different elevations in a 3-D integrated photonic circuit. Transfer of optical power carried by planar, semi-guided waves is possible without reflections or radiation losses, and over large vertical distances. This functionality is realized through simple step-like folds of high-contrast dielectric slab waveguides, in combination with oblique wave incidence, and fulfilling a resonance condition. Radiation losses vanish, and polarization conversion is suppressed for TE wave incidence beyond certain critical angles. This can be understood by fundamental arguments resting on a version of Snell’s law. The two 90° corners of a step act as identical partial reflectors in a Fabry–Perot-like resonator setup. By selecting the step height, i.e., the distance between the reflectors, one realizes resonant states with full transmission. Rigorous quasi-analytical simulations for typical silicon/silica parameters demonstrate the functioning. Combinations of several step junctions can lead to other types of optical on-chip connects, e.g., U-turn- or bridge-like configurations.
Keywords: tet_topic_waveguide

Subwavelength binary plasmonic solitons - Kou, Yao; Förstner, Jens (Optics Letters)
We study the formation of subwavelength solitons in binary metal-dielectric lattices. We show that the transverse modulation of the lattice constant breaks the fundamental plasmonic band and suppresses the discrete diffraction of surface plasmon waves. New types of plasmonic solitons are found, and their characteristics are analyzed. We also demonstrate the existence of photonic-plasmonic vector solitons and elucidate their propagation properties.
Keywords: tet_topic_polariton

Robust Population Inversion by Polarization Selective Pulsed Excitation - Mantei, D.; Förstner, Jens; Gordon, S.; Leier, Y. A.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Zrenner, Artur (Scientific Reports)
The coherent state preparation and control of single quantum systems is an important prerequisite for the implementation of functional quantum devices. Prominent examples for such systems are semiconductor quantum dots, which exhibit a fine structure split single exciton state and a V-type three level structure, given by a common ground state and two distinguishable and separately excitable transitions. In this work we introduce a novel concept for the preparation of a robust inversion by the sequential excitation in a V-type system via distinguishable paths.
Keywords: tet_topic_qd

How do reviews from professional critics interact with other signals of product quality? Evidence from the video game industry - Cox, Joe; Kaimann, Daniel (Journal of Consumer Behaviour)
Experience goods are characterised by information asymmetry and a lack of ex ante knowledge of product quality, such that reliable external signals of quality are likely to be highly valued. Two potentially credible sources of such information are reviews from professional critics and ‘word of mouth’ from other consumers. This paper makes a direct comparison between the relative influences and interactions of reviews from both of these sources on the sales performance of video game software. In order to empirically estimate and separate the effects of the two signals, we analyze a sample of 1480 video games and their sales figures between 2004 and 2010. We find evidence to suggest that even after taking steps to control for endogeneity, reviews from professional critics have a significantly positive influence on sales which outweighs that from consumer reviews. We also find evidence to suggest that reviews from professional critics also interact significantly with other signals of product quality. Consequently, we contend that professional critics adopt the role of an influencer, whereas word-of-mouth opinion acts more as a predictor of sales in the market for video games.

How do Different Sources of the Variance of Consumer Ratings Matter? - Herrmann, Philipp; Kundisch, Dennis; Zimmermann, Steffen; Nault, Barry (Proceedings of the 36th International Conference on Information Systems (ICIS), Fort Worth)
We examine the effect of the variance of consumer ratings on product pricing and sales using an analytical model, which considers goods that are characterized by experience attributes and informed search attributes (i.e., experience attributes that were transformed in search attributes by consumer ratings). For pure informed search goods, equilibrium price increases and demand decreases in variance. For pure experience goods, equilibrium price and demand decrease in variance. For hybrid goods with low total variance, equilibrium price and demand increase with an increasing relative share of variance caused by informed search attributes when the average rating and total variance of ratings are held constant. Hence, risk-averse consumers may prefer a more expensive good with a higher variance of ratings out of two similar goods with the same average rating. Moreover, our analytical model provides a theoretical foundation for the empirically observed j-shaped distribution of consumer ratings in electronic commerce.

Grammar-based model transformations: Definition, execution, and quality properties - Besova, Galina; Steenken, Dominik; Wehrheim, Heike (Computer Languages, Systems & Structures)
Model transformation is a key concept in model-driven software engineering. The definition of model transformations is usually based on meta-models describing the abstract syntax of languages. While meta-models are thereby able to abstract from uperfluous details of concrete syntax, they often loose structural information inherent in languages, like information on model elements always occurring together in particular shapes. As a consequence, model transformations cannot naturally re-use language structures, thus leading to unnecessary complexity in their development as well as in quality assurance.In this paper, we propose a new approach to model transformation development which allows to simplify the developed transformations and improve their quality via the exploitation of the languages׳ structures. The approach is based on context-free graph grammars and transformations defined by pairing productions of source and target grammars. We show that such transformations have important properties: they terminate and are sound, complete, and deterministic.

Fuzzy Matching von Vor- und Nachbedingungen in Servicespezikationen - Börding, Paul

Fusionen von gesetzlichen Krankenversicherungen zu den Effizienz- und Wechselwirkungen - Osburg, Christina

Tightly-Secure Signatures from Chameleon Hash Functions - Blazy, Olivier; Kakvi, Saqib; Kiltz, Eike; Pan, Jiaxin (Lecture Notes in Computer Science)

Filtering Reviews by Random Individual Error - Geierhos, Michaela; Bäumer, Frederik Simon; Schulze, Sabine; Stuß, Valentina (Proceedings of the 28th International Conference on Industrial, Engineering and Other Applications of Applied Intelligent Systems (IEA/AIE 2015))
Opinion mining from physician rating websites depends on the quality of the extracted information. Sometimes reviews are user-error prone and the assigned stars or grades contradict the associated content. We therefore aim at detecting random individual error within reviews. Such errors comprise the disagreement in polarity of review texts and the respective ratings. The challenges that thereby arise are (1) the content and sentiment analysis of the review texts and (2) the removal of the random individual errors contained therein. To solve these tasks, we assign polarities to automatically recognized opinion phrases in reviews and then check for divergence in rating and text polarity. The novelty of our approach is that we improve user-generated data quality by excluding error-prone reviews on German physician websites from average ratings.

Fair Trade - Eine neue Perspektive in der internationalen Handelspolitik - Materna, GinaJoanna

Fair Trade - An economic investigation of benefits and drawbacks - Goronczewski, Patricia

Evaluation of Pairing Optimization for Embedded Platforms - Sosniak, Martin

Entwicklung von Ablösesummen und Gehälter in der Fußball-Bundesliga - Salary Caps als mögliches Modell der Chancengleichheit - Plonka, Dennis

Elektromagnetische Seitenkanalangriffe auf paarungsbasierte Kryptographie - Gerken, Britta

Ausgewählte Probleme des Logistikmanagements

Ein Framework für Fuzzy Service Matching basierend auf Fuzzy Sets - Neumann, Conrad

Efficient Verifier-Local Revocation for Anonymous Credentials - Bobolz, Jan

Efficient Attributes for Pairing-Based Anonymous Credentials - Stroh, Christian

Dynamics and Efficiency in Topological Self-Stabilization - Koutsopoulos, Andreas

Distributed Data Structures and the Power of topological Self-Stabilization - Kniesburges, Sebastian

Diffusion of Innovations in Social Networks - Kunisch, Christina

Die Wirksamkeit von Zertifikaten als Qualitätssignal - Reimann, Alina

Die Einführung der EU-Merger Guidelines - Effizienz und Wohlfahrtswirkungen - Topal, Barlas

Design of an Evaluation Strategy for Fuzzy Service Matching - Bruns, Melanie

Constructions of Fully Secure Predicate Encryption Schemes - Schleiter, Patrick

Confined Guessing: New Signatures From Standard Assumptions - Böhl, Florian; Hofheinz, Dennis; Jager, Tibor; Koch, Jessica; Striecks, Christoph (J. Cryptology)

On the Security of TLS 1.3 and QUIC Against Weaknesses in PKCS#1 v1.5 Encryption - Jager, Tibor; Schwenk, Jörg; Somorovsky, Juraj (Proceedings of the 22nd ACM SIGSAC Conference on Computer and Communications Security, Denver, CO, USA, October 12-16, 2015)

Practical Invalid Curve Attacks on TLS-ECDH - Jager, Tibor; Schwenk, Jörg; Somorovsky, Juraj (Computer Security - ESORICS 2015 - 20th European Symposium on Research in Computer Security, Vienna, Austria, September 21-25, 2015, Proceedings, Part I)

On the Selective Opening Security of Practical Public-Key Encryption Schemes - Heuer, Felix; Jager, Tibor; Kiltz, Eike; Schäge, Sven (Public-Key Cryptography - PKC 2015 - 18th IACR International Conference on Practice and Theory in Public-Key Cryptography, Gaithersburg, MD, USA, March 30 - April 1, 2015, Proceedings)

One-Round Key Exchange with Strong Security: An Efficient and Generic Construction in the Standard Model - Bergsma, Florian; Jager, Tibor; Schwenk, Jörg (Public-Key Cryptography - PKC 2015 - 18th IACR International Conference on Practice and Theory in Public-Key Cryptography, Gaithersburg, MD, USA, March 30 - April 1, 2015, Proceedings)

Verifiable Random Functions from Weaker Assumptions - Jager, Tibor (Theory of Cryptography - 12th Theory of Cryptography Conference, TCC 2015, Warsaw, Poland, March 23-25, 2015, Proceedings, Part II)